Dry deposition of particles to canopies—A look back and the road forward. Issue 24 (22nd December 2016) - Hicks, Bruce B.; Saylor, Rick D.; Baker, Barry D.
Abstract: The so‐called accumulation‐size range of airborne particles is the center of a continuing disagreement about the formulation of dry deposition. Some contemporary meteorological and air quality models use theoretical developments based on early wind tunnel and other controlled experiments, while other models consider the bulk properties of the underlying surface and the ability of atmospheric turbulence to deliver particles to it. This dichotomy arose when the first micrometeorological measurements of particle deposition velocities became available, yielding numbers exceeding the highest expectations of the then‐current models based on assumptions about inertial impaction and interception. The model predictions had previously been shown to be in accord with theoretical treatments of filtration. A common reaction was to distrust the field experimental results, but the experimental findings were supported by subsequent studies. The difference between model predictions and field measurements appears greatest for densely vegetated canopies. Ongoing research is investigating factors that could give rise to the discrepancy, e.g., turbulence intermittency, leaf orientation, leaf morphology, leaf flutter, electrical charges, and a number of phoretic effects. In the meantime, many investigators are faced with a decision as to whether to make use of parameterized field results or theoretical descriptions of behaviors that are not yet well examined. Here the history of the ongoing disagreement is reviewed, and some possible resolutions are presented. Key Points: Some models fail to acknowledge actual particle deposition data Reasons for differences between observations and predictions remain obscure Modern instrumentation allows the matter to be addressed experimentally